2020
DOI: 10.3389/fphys.2020.01107
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of the Nematode Caenorhabditis elegans in Acidic Stress Environments

Abstract: Ocean acidification and acid rain, caused by modern industries' fossil fuel burning, lead to a decrease in the living environmental pH, which results in a series of negative effects on many organisms. However, the underlying mechanisms of animals' response to acidic pH stress are largely unknown. In this study, we used the nematode Caenorhabditis elegans as an animal model to explore the regulatory mechanisms of organisms' response to pH decline. Two major stress-responsive pathways were found through transcri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Previously, Dodd et al (2018) has shown that multiple cuticle collagen genes can be induced when C. elegans exposed to high NaCl. Recently, we reported that a battery of collagen genes in C. elegans increased their expression to deal with acidic pH stress environments ( Cong et al, 2020 ). Together, these results indicated a protective role of collagens in response to various stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Dodd et al (2018) has shown that multiple cuticle collagen genes can be induced when C. elegans exposed to high NaCl. Recently, we reported that a battery of collagen genes in C. elegans increased their expression to deal with acidic pH stress environments ( Cong et al, 2020 ). Together, these results indicated a protective role of collagens in response to various stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Establishment of a terrestrial-marine relative nematodes pair model for developmental evolution and environmental adaptation C. elegans is widely used as a biomedical model organism. Its short life span, ease of handling and maintenance, clear genetic background and advanced genetic and molecular biology tools together, make C. elegans a powerful model to study development, neurobiology, longevity, and stress responses (Zhang et al, 2015b;Cong et al, 2020b). During the 20th century, the transition in biology from description to mechanistic understanding was largely due to widely employed model organisms (Russell et al, 2017).…”
Section: Evo-devo and Adaptation To The Global Climate Change In Marine Model Nematode (Figure 12)mentioning
confidence: 99%
“…However, the underlying mechanisms are largely unexplored. Recently, we employed RNA-Seq (RNA Sequencing) to ask how the terrestrial nematode C. elegans and the marine nematode L. marina respond to the acidic pH stresses, respectively (Cong et al, 2020b;Cong et al, 2020a). Two major response strategies to the reduced pH were found in C. elegans.…”
Section: Nematode Developmental Evolution and Response To Global Climate And Environment Changementioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Dodd et al has shown that multiple cuticle collagen genes can be induced when C. elegans exposed to high NaCl (Dodd et al, 2018). Recently, we reported that a battery of collagen genes in C. elegans increased their expression to deal with acidic pH stress environments (Cong et al, 2020). Together, these results indicated a protective role of collagens in response to various stresses.…”
Section: Discussionmentioning
confidence: 99%